A developmental staging system and musculoskeletal development sequence of the common musk turtle (Sternotherus odoratus). Issue 1 (4th August 2020) - Smith Paredes, Daniel; Lord, Arianna; Meyer, Dalton; Bhullar, Bhart‐Anjan S.
Abstract: Background: The extremely derived body plan of turtles has sparked a great interest in studying their developmental biology. Here, we describe the embryonic development of the Stinkpot, or common musk turtle ( Sternotherus odoratus ), a small aquatic turtle from the family Kinosternidae. Results: We identify 20 distinct developmental stages, some comparable to stages described by previous studies on other turtles and some in between these, improving the resolution of the generalities of turtle development. We provide a detailed account of both the external morphology and skeletal development, as well as a general look at the early stages of muscular development until the attainment of the adult muscular anatomical pattern. Conclusions: Several potential skeletal and muscular apomorphies of turtles are identified or elaborated. The musk turtle, with its small size and hard‐shelled egg, could become an important species for the study of turtle evolution and development, suitable for in ovo experimentation and late stage imaging of well‐advanced anatomical features. Key Findings: We describe the external, skeletal and muscular development of the Common musk turtle, Sternotherus odoratus, a turtle from the family Kinosternidae, for which their development was previously underscribed. We show in great detail the developing pattern and peculiarities of the anatomy of this turtle, and propose it as a useful species for both the study of turtle and reptile development and evolution